A vignette model for distributed teaching and learning - Marcel Chaloupka; Tony Koppi (Association for Learning Technology, 1998)
The notion of convergence of disparate technologies has become popular with governments, computing and business sectors in the 1990s; but how has the convergence been implemented in the educational sector? One evident area of convergence in education has been the use of the Internet. But according to Gosper et al (1996), the most likely strategies for implementation are to use the Internet as a repository of reference, lecture materials and the presentation of the lectures. This could imply that the full potential of distributed learning through convergence might never be achieved. How can we implement good learning strategies following sound educational methodologies today, while not producing legacy systems or piecemeal content that could constrain future developments? In making it possible for distributed learning to occur, there are best-practice considerations applicable to most educational environments.